COVID-19: A GREAT CHALLENGE FOR THE TOURISM INDUSTRY - Akhtar (MPH), Naushaba (Journal of Biomedical and Pharmaceutical Research, 2021)
The COVID-19 pandemic is one of those disasters which caused massive damage to human and property. Most of the countries have faced their impact massively as it affects the people and business adversely. As this pandemic affected all the sectors, the tourism sector was not left behind. A major impact was seen in outbound tourism and both travel and tourism has equally faced a greater challenge than any other industry in most of the nations. This paper aims to investigate the extent of the impact of COVID-19 on Tourism industry during the pandemic.